Giudicare l'arte Le corti degli Stati Uniti e la libertà di espressione artistica - palandri, lucrezia (Premio Tesi di Dottorato, 2016)
This volume examines how the definition of art is not to be considered the prerogative of philosophical and aesthetic disciplines, but should rather assume decisive importance for the legal protection of the art object. Based on this premise, this work retraces the evolution of the concept of art and its limits in the case law of US courts, focusing on the constitutional aspect of the freedom of artistic expression. This volume notes how the cases in which judges must decide whether or not an object constitutes a work of art can say much more about the nature of judgement than about the nature of art itself.